Exploring potential ecotourism products in Sabah, Malaysia / Velan Kunjuraman and Rosazman Hussin. - Kunjuraman, Velan; Hussin, Rosazman (Universiti Teknologi Mara Selangor, 2019)
In line with the vision of sustainable development goals, ecotourism may be regarded as a tool for human awareness to protect the natural environment and local community development. Since ecotourism relies on natural resources and setting in rural areas, community participation is considered as a viable method to achieve sustainable ecotourism development as well as to enhance local community sustainable livelihoods. This study aims to investigate the potential of ecotourism products in the Ramsar site of the lower Kinabatangan area of Sabah, East Malaysia, as a sustainable livelihood activity for the villagers. The fieldwork was conducted between September to November 2014. This study used multiple data collection methods such as in-depth and focus group interviews, household survey through questionnaire, and field observation in order to support the research findings. There are many potential ecotourism products based on the natural environment that could be developed in the Ramsar site and local participation is vital in the development of the products. Finally, several recommendations to promote the natural attractions along the Ramsar site by relevant stakeholders are highlighted.